2012
DOI: 10.1111/j.1524-475x.2012.00769.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of planktonic and biofilm MRSA on human fibroblasts

Abstract: Bacteria colonizing chronic wounds often exist as biofilms, yet their role in chronic wound pathogenesis remains unclear. Staphylococcus aureus biofilms induce apoptosis in dermal keratinocytes, and given that chronic wound biofilms also colonize dermal tissue, it is important to investigate the effects of bacterial biofilms on dermal fibroblasts. The effects of a predominant wound pathogen, methicillin-resistant S. aureus, on normal, human, dermal fibroblasts were examined in vitro. Cell culture medium was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
81
2
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(88 citation statements)
references
References 40 publications
(65 reference statements)
2
81
2
3
Order By: Relevance
“…Biofilms protect bacteria from opsonization, antibiotic exposure, and phagocytosis (4)(5)(6). Staphylococcus aureus, a common human pathogen, is often associated with biofilm infections (7)(8)(9) in chronic wounds (8,10,11). Such infections are problematic to treat because of the slow penetration of antimicrobials and antibiotics through the biofilm matrix (10,(12)(13)(14) and the formation of persister cells (15).…”
mentioning
confidence: 99%
“…Biofilms protect bacteria from opsonization, antibiotic exposure, and phagocytosis (4)(5)(6). Staphylococcus aureus, a common human pathogen, is often associated with biofilm infections (7)(8)(9) in chronic wounds (8,10,11). Such infections are problematic to treat because of the slow penetration of antimicrobials and antibiotics through the biofilm matrix (10,(12)(13)(14) and the formation of persister cells (15).…”
mentioning
confidence: 99%
“…Some studies have shown that bacterial biofilms induce an increase of IL-6 and IL-8 (Eberhard et al, 2009;Cantero et al, 2013a,b). Some studies have reported that planktonic bacteria cause the body to produce more IL-6, IL-8, vascular endothelial growth factor, and transforming growth factor beta 1 compared with biofilm bacteria, while biofilm bacteria induce more tumor necrosis factor alpha (Kirker et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…A study by Kirker et al [9] showed that wound healing can be accelerated in the presence of non-viable S. aureus as a result of the contribution by its cell wall and cell wall peptidoglycan components, which enhances number and alteration in location of phagocytes, increased proliferation of mesenchymal cells (notably fibroblasts), and increased angiogenesis and reparative collagen accumulation, as well as increasing the overall acute inflammatory response to injury [9].…”
Section: Introductionmentioning
confidence: 99%
“…Risk factors include poor sanitation and poor hygiene [9]. Escherichia coli are a gram-negative, facultative anaerobe [11], with most strain harmless, but some serotypes can cause serious food poisoning in their hosts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation